Copper-mediated cascade radical cyclization of olefins with naphthalenyl iododifluoromethyl ketones - Peng, Peng; Huang, Guo-zhi; Sun, Ying-xin; Wang, Xing; Wu, Jing-jing; Wu, Fan-hong (Organic & biomolecular chemistry, 2019)
Copper-mediated radical cyclization of naphthalenyl iododifluoromethyl ketones with olefins was successfully developed to generate a series of unprecedented gem -difluorodihydrophenanthrenones, especially 2,2-difluoro-3,4-dihydrophenanthren-1(2 H )-one derivatives. This strategy features the use of cheap copper powder and excellent regioselectivity and diastereoselectivity, thus providing a facile approach for application in drug discovery and development. Preliminary mechanistic studies indicate the involvement of difluorinated radical intermediates. Density functional theory (DFT) calculation was performed to provide further evidence for regioselectivity. Copper-mediated radical cyclization of naphthalenyl iododifluoromethyl ketones with olefins was developed to generate a series of unprecedented gem -difluorodihydrophenanthrenones with excellent regioselectivity.